Sex-based Differences in the Association between Body Composition and Incident Fracture Risk in Koreans - Kim, Jung Hee; Hong, A. Ram; Choi, Hyung Jin; Ku, Eu Jeong; Cho, Nam H.; Shin, Chan Soo (Scientific reports, 2017)
The relative contribution of lean mass and fat mass on bone health is inconclusive. We investigated the relative contributions of lean and fat masses on fragility fracture risk in Korean men and women. This was an ongoing prospective community-dwelling cohort study at Ansung beginning in 2001, which included 2,189 men and 2,625 women over 40 years old. Study subjects were classified into the following four groups according to lean mass (LM)/height 2 and percentage fat mass (PF). Clinical fragility fracture events were assessed at baseline and biennially using self-reported questionnaires. During a median follow-up of 9.4 years, 77 (3.5%) men and 203 (7.7%) women experienced at least one incident fracture. In Cox proportional hazard models, men with low LM under normal and high PF had a 2.16 and 2.59- fold higher risk for fragility fractures than normal ones even after adjusting for covariates. However, in women, low LM or high FM was not associated with fracture risk. We demonstrated sex-based differences in the association of body composition and incident fracture risk in Koreans aged over 40 years during a 10-year follow-up duration. Maintaining muscle mass in men is vital to maintaining bone health and preventing fragility fractures in Koreans.